HEDGING SEBAGAI PEMEDIASI PADA PENGARUH FINANCIAL DISTRESS TERHADAP FIRM VALUE - Ng, Suwandi; Daromes, Fransiskus E. (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2024)
The purpose of this study is to examine how financial distress affects firm value while using hedging as a kind of mediation. This research model uses stakeholder theory and signal theory. Explanatory research falls under this category. Data was gathered from businesses in the consumer goods category that were listed on the Indonesian Stock Exchange between 2018 and 2020. Regression analytic techniques, and Sobel tests are all used in this study to examine the role of hedging as a mediating variable. The findings of this study demonstrate that financial distress significantly affects hedging and corporate value. In addition, the Sobel test's findings demonstrate that hedging mediates the impact of financial distress on firm value.